Assessment and numerical validation of a normal mode stability analysis for conjugate heat transfer. (1st August 2022) - Gelain, Matteo; Errera, Marc-Paul; Gicquel, Olivier
Highlights: Normal mode stability analysis performed on counjugate heat transfer (CHT) 1D problem. Stability analysis reveals existence of lower stability bound for coupling coefficient in Robin-Dirichlet interface boundary conditions. Validity of stability analysis results is verified empirically. Stability analysis is extended to more general CHT problems. Abstract: This paper aims to evaluate and validate a mathematical coupling model, based on a normal mode stability analysis, for steady conjugate heat transfer problems. In order to achieve this goal, an aerothermal computational code was designed specifically ex novo to meet the needs of the current study. A large number of numerical simulations were carried out within the framework of the Dirichlet-Robin fluid-solid interface procedure and with conditions strictly identical to those adopted in the mathematical model. These coupled computations have been synthesized in five representative cases. The computed results show that the stability limit and the numerical Biot number derived from the coupling model are very reliable parameters. Many other physical and numerical aspects, such as the splitting of the coupling period are also considered in this work from which some interesting and promising results are obtained. At the end of this paper, we assess the general potential, limits and constraints of the mathematical model and its extension to multidimensional cases is discussed.